Effect of N‐palmitoylethanolamine‐oxazoline on comorbid neuropsychiatric disturbance associated with inflammatory bowel disease. Issue 3 (16th January 2020) - Cordaro, Marika; Scuto, Maria; Siracusa, Rosalba; D'amico, Ramona; Filippo Peritore, Alessio; Gugliandolo, Enrico; Fusco, Roberta; Crupi, Rosalia; Impellizzeri, Daniela; Pozzebon, Michele; Alfonsi, Daniele; Mattei, Nicolò; et al.
Abstract: Inflammatory bowel disease (IBD) is a chronic disorder characterized by inflammation of the gastrointestinal (GI) tract, and it is associated with different neurological disorders. Recent evidence has demonstrated that the gut‐brain‐axis has a central function in the perpetuation of IBS, and for this reason, it can be considered a possible therapeutic target. N‐Palmitoylethanolamine‐oxazoline (PEA‐OXA) possesses anti‐inflammatory and potent neuroprotective effects. Although recent studies have explained the neuroprotective properties of PEA‐OXA, nothing is known about its effects on the gut‐brain axis during colitis. The aim of this study is to explore the mechanism and the effect of PEA‐OXA on the gut‐brain axis in rats subjected to experimental colitis induced by oral administration of dextran sulfate sodium (DSS). Daily oral administration of PEA‐OXA (10 mg/kg daily o.s.) was able to decrease the body weight loss, macroscopic damage, colon length, histological alteration, and inflammation after DSS induction. Additionally, PEA‐OXA administration enhanced neurotrophic growth factor release and decreased the astroglial and microglial activation induced by DSS. Moreover, PEA‐OXA restored intestinal permeability and tight junctions (TJs) as well as reduced apoptosis in the colon and brain. In our work, we demonstrated, for the first time, the action of PEA‐OXA on the gut‐brain axis in a model of DSS‐induced colitis and its implication on the "secondary" effects associated with colonic disturbance.